Proceedings of the 2019 International Conference on Education Science and Economic Development (ICESED 2019) 2020
DOI: 10.2991/icesed-19.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Central Business District on House Market Price: a Case Study of Nanchang City, China

Abstract: It is significant to make clear the influence of the city's central business district (CBD) on the surrounding house market price (HMP), which is reflected by the following indicators: rental and purchase price. Thus, taking Nanchang of China as a case, we choose two CBDs (Bayi Square and Honggutan) to further study this issue in this paper by using the linear regression model. The results showed: with the growth of the distance between the studied community and the CBD, the community's HMP appeared a diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The findings indicate that distance of the Unsold New Houses to the Nairobi CBD (B = 0.219, P < 0.05) was significant predictors of the duration of unsold new houses. The results support the findings of a study conducted by Jia et al (2020) that found the 1 km growth of the distance between the community and the CBD in Bayi Square led to a decrease in the rental and purchase houses. The results also support the findings of Bich et al (2020) who measured the dynamic effect on probability of selling a house against distance to CBD and concluded that distance to CBD has a positive and significant effect on the probability of a sale with a 1.23% increase in the probability that a property will be sold as the distance from the development reduces.…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 3 more Smart Citations
“…The findings indicate that distance of the Unsold New Houses to the Nairobi CBD (B = 0.219, P < 0.05) was significant predictors of the duration of unsold new houses. The results support the findings of a study conducted by Jia et al (2020) that found the 1 km growth of the distance between the community and the CBD in Bayi Square led to a decrease in the rental and purchase houses. The results also support the findings of Bich et al (2020) who measured the dynamic effect on probability of selling a house against distance to CBD and concluded that distance to CBD has a positive and significant effect on the probability of a sale with a 1.23% increase in the probability that a property will be sold as the distance from the development reduces.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…The distance of a residential property to the urban center's Central Business District (CBD) could influence its demand and thus affect UNHS. CBD is one of the kernel of the city characterized by more and better resources of floating population, finance, technology, infrastructure and education when compared to other locations in the Country (Dziauddin & Misran, 2016;Jia, Rong, Gu, & Xie, 2020). The net population declines with the location moves away from the CBD and there is a drop in demand for housing as the distance from CBD rise (McDonald, 2020).…”
Section: Empirical Reviewmentioning
confidence: 99%
See 2 more Smart Citations